Ambiguitas sanksi hukum terhadap masyarakat yang menolak vaksinasi Covid-19 - Ali Imran Nasution; Wicipto Setiadi; Yusuf Eko Nahuddin (University of Merdeka Malang, 2021)
In 2020, the President of Indonesia established Presidential Regulation Number 99 of 2020 concerning the Procurement and Implementation of Vaccinations to Annihilate Covid-19 Pandemic. Furthermore, this Presidential Regulation was amended by Presidential Regulation Number 14 of 2021 which contained a particular provision to impose legal sanctions on people who violated rules by do not participate in Covid-19 vaccination. Administration sanctions such as postponing or terminating social security awarding or social assistance will be imposed on a citizen who does not comply with that particular provision. This kind of administrative sanction will potentially harm the rights of lower classes people. This study is to analyze the ambiguity of legal sanctions against people who refuse to get Covid-19 vaccination and to analyze the alternative solution to take out the ambiguity of imposing sanctions on people who violated these particular rules. This research method uses normative legal research by statutory and conceptual approach. This study concludes that the ambiguity caused by those sanctions is contradicted with the legislation rules and principles. Therefore, social work sanctions can be used as an alternative solution to substitute administrative sanctions that cause ambiguity and violated the community’s rights.How to cite item: Nasution, A., Setiadi, W., Nahuddin, Y. (2021). Ambiguitas sanksi hukum terhadap masyarakat yang menolak vaksinasi Covid-19. Jurnal Cakrawala Hukum, 12(3), 233-244. doi:https://doi.org/10.26905/idjch.v12i3.6417.